1995
DOI: 10.1074/jbc.270.39.22788
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Yeast Translation Initiation Factor 1A and Cloning of Its Essential Gene

Abstract: Translation initiation factor eIF1A is required in vitro for maximal rates of protein synthesis in mammalian systems. It functions primarily by dissociating ribosomes and stabilizing 40 S preinitiation complexes. To better elucidate its precise role in promoting the translation initiation process, the yeast form of eIF1A has been identified in Saccharomyces cerevisiae and purified to homogenity on the basis of its cross-reaction with antibodies prepared against mammalian eIF1A. The apparent mass of yeast eIF1A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 36 publications
3
29
0
Order By: Relevance
“…The presence of eIF1A in the 40 S initiation complex was also shown in one of these earlier studies (9). In vivo studies in Saccharomyces cerevisiae demonstrated that the genes encoding these two small initiation factors are essential for initiation of protein synthesis and required for cell growth and viability (12)(13)(14). These observations are in accord with genetic studies in S. cerevisiae (15,16) that indicate that eIF1 (SUI 1) plays an essential role in the fidelity of start site selection.…”
supporting
confidence: 79%
“…The presence of eIF1A in the 40 S initiation complex was also shown in one of these earlier studies (9). In vivo studies in Saccharomyces cerevisiae demonstrated that the genes encoding these two small initiation factors are essential for initiation of protein synthesis and required for cell growth and viability (12)(13)(14). These observations are in accord with genetic studies in S. cerevisiae (15,16) that indicate that eIF1 (SUI 1) plays an essential role in the fidelity of start site selection.…”
supporting
confidence: 79%
“…We used yeast two-hybrid assays to identify and then localize the eIF1A-interacting region in eIF5B. A series of GAL4 DNA binding domain and GAL4 activation domain fusions containing various truncated fragments of yeast eIF5B were tested for interaction with the appropriate fusions containing the full-length 153-amino-acid yeast eIF1A (43) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Cultures were grown at 30ЊC and were monitored by measuring the optical density at 600 nm (OD 600 ). For sporulation (20), cells were grown on YPD plates (containing 6% glucose) for 24 h and then were sporulated at room temperature on plates modified for strain W303 (27) containing 0.3% potassium acetate, 0.02% raffinose, and 10 g of each amino acid per ml. Tetrad dissections and DNA transformations were carried out by using standard procedures (25).…”
Section: Methodsmentioning
confidence: 99%